Karama Has No Walls - Ishaq, Sara (United Kingdom, 2012)
This film is an illustration of the calm nature of the Yemeni revolution, which is in stark contrast with the human rights violations that took place on the Friday of Dignity. Pro-government snipers shot 53 protesters dead and injured thousands, marking a turning point in Yemen’s revolution. Through the lenses of two cameramen and the accounts of two fathers, the film encapsulates the tragic events of this day.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films